IMPLEMENTATION OF MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) ON THE INTEREST OF MOESTOPO UNIVERSITY STUDENTS - Meiliyah Ariani; Zulhawati (Universitas prof. Dr. Moestopo (Beragama), 2022)
Merdeka Belajar Kampus Merdeka (MBKM) Policy is the right to study for three semesters, namely completing 1 semester (equivalent to 20 credits) and 2 semesters (equivalent to 40 credits) in different study programs at the same university or the same study program at the university. different. The purpose of the research is to prove the effect of student exchange activities, internships or work practices, campus teaching, research or research, humanitarian projects, entrepreneurship, independent studies or projects, and building villages or KKNT in the MBKM program on the interest of students of the Faculty of Economics and Business Moestopo University. The data used in this study is primary data. The sampling technique used purposive sampling technique with 100 respondents. The method used is a multiple regression technique using SPSS 26. The results show that the independent variables of campus teaching, research or research, humanitarian projects, independent studies or projects, and building a village or KKNT have no significant effect on student interest. But the independent variables of student exchange, internship or work practice, and entrepreneurship have a significant effect on interest in learning.